Технічні вимоги для бізнес-користувачів: застосування системи забезпечення якості для програмного забезпечення - Haigh, Maria (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
We conducted a survey of more than 300 business stakeholders, asking them to specify their views on software quality requirements within established quality framework. The results showed business role-related differences in specific areas. The paper also considers the implications of these results and their relevance to software requirements analysis.